2021
DOI: 10.21203/rs.3.rs-155736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid p-tau231 as an early indicator of emerging pathology in Alzheimer’s disease

Abstract: Biomarkers for early phosphorylation of tau constitute an unmet need for disease modifying intervention in early stages of Alzheimer’s disease (AD). Recent advances in targeted mass spectrometry and immunoassays have revealed phosphorylation sites, in the cerebrospinal fluid (CSF), with potentially greater utility as preclinical and diagnostic biomarkers as compared to the well validated biomarker – phosphorylated tau at threonine 181 (p-tau181). Phosphorylated tau (p-tau) epitopes in cerebrospinal fluid (CSF)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 61 publications
8
28
0
Order By: Relevance
“…The horizontal grey bars shows the mean and 95% confidence intervals (CI) of plasma p-tau231 and p-tau181 as well as CSF p-tau217 in elderly individuals (CU, MCI, AD) segregated Aβ PET quartiles. Plasma p-tau231 showed abnormally increased levels from Aβ PET quartile 2 to 4; plasma p-tau181 in quartile 4, and CSF in quartiles [3][4] However, it demonstrated, much like the CSF comparisons that have preceded this study, that plasma p-tau231 was not significantly superior nor inferior to plasma p-tau181 in the aforementioned analysis. One exception to this being plasma p-tau231 being able to distinguish CU Aβ-positive participants from Aβ-negative MCI cases with higher accuracy and significantly superior to plasma p-tau181 (supplementary table 7, online resource).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The horizontal grey bars shows the mean and 95% confidence intervals (CI) of plasma p-tau231 and p-tau181 as well as CSF p-tau217 in elderly individuals (CU, MCI, AD) segregated Aβ PET quartiles. Plasma p-tau231 showed abnormally increased levels from Aβ PET quartile 2 to 4; plasma p-tau181 in quartile 4, and CSF in quartiles [3][4] However, it demonstrated, much like the CSF comparisons that have preceded this study, that plasma p-tau231 was not significantly superior nor inferior to plasma p-tau181 in the aforementioned analysis. One exception to this being plasma p-tau231 being able to distinguish CU Aβ-positive participants from Aβ-negative MCI cases with higher accuracy and significantly superior to plasma p-tau181 (supplementary table 7, online resource).…”
Section: Discussionmentioning
confidence: 48%
“…This demonstrates that soluble tau, in CSF and plasma, is likely indicative of early tau pathology which is closely correlated with Aβ deposition. We have recently described the increase of different phosphoforms of tau in CSF in preclinical and prodromal disease [3,28,58]. In two independent studies [3,58], we found that CSF p-tau phosphorylated at threonine 231 (p-tau231) is a biomarker of very early tau pathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies have since confirmed that CSF p-tau181 can be used to differentiate AD from other dementias, such as frontotemporal dementia (FTD) and dementia with Lewy bodies [91][92][93]. Recently, five studies have shown that CSF p-tau217 perform somewhat better than CSF p-tau181 when differentiating AD from non-AD diseases [92][93][94][95][96]. These findings have now been largely replicated using blood p-tau.…”
Section: Phase 2: Primary Aimmentioning
confidence: 97%